Redecoration and Room Makeover Tendencies - Yasmin Zainul Mochtar; Prasetyo Wahyudie; Susy Budi Astuti; Lea Kristina Anggraeni; Anggra Ayu Rucitra; Onna Anieqo Tanadda (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DRPM), ITS, 2022)
This research was conducted by using the result of a practical examination for Home Décor enrichment class in Interior Design Department 100 undergtaduate tudents consisting of interior design students and non-interior design students were each assigned to redecorate or makeover one specific room or spot within their home. The students were asked to provide the before and after pictures of the room that they had redecorated. A quantitative study method is used in this research. The result pictures from the assignment are then observed one by one and put in a digital questionnaire and deducted as data. The aim of this study is to observe the tendencies of redecorating and room makeover, to see how much of these redecorating and makeover tendencies would affect the end result of the redecorated room. The research shows that an optimum redecoration and makeover results from a combination of change in both interior elements (interior form and interior filler), reorganizing positions of interior filler and also adding or removing items from the room.